Don’t Look Back In Anger: The Mythic World-building of Melinda Salisbury’s Her Dark Wings - Ash Bond (Leaf Journal)
Through a close reading of Her Dark Wings by Melinda Salisbury and Ash Bond’s own work-in-progress this article examines the use of mythology as a megatext. It explores how both texts handle alternate narratives existing in parallel, and the use of the Underworld as a realm of initiation and transformation. It concludes that while the framework of myth can attract the reader, the subversion of an expected mythic narrative can be a useful tool to incite a reader’s curiosity and propel them through the story.